Switching between GLP‐1 receptor agonists in clinical practice: Expert consensus and practical guidance. Issue 2 (3rd November 2020) - Jain, Akshay B.; Ali, Amar; Gorgojo Martínez, Juan J.; Hramiak, Irene; Kavia, Ketan; Madsbad, Sten; Potier, Louis; Prohaska, Ben D.; Strong, Jodi L.; Vilsbøll, Tina
Abstract: Background: Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are an established treatment for patients with type 2 diabetes (T2D). Differences between GLP‐1RAs in pharmacokinetics, dosing regimens and clinical effects, including cardiovascular (CV) outcomes, mean there may be benefits to switching from one to another. However, clinical guidance on switching is lacking and data from clinical trials are limited. This article provides a clinical perspective and consensus on the benefits of switching between GLP‐1RAs, the triggers for switching and how best to manage this in clinical practice. Once weekly (OW) semaglutide is used as an example to illustrate how the authors might switch to a different GLP‐1RA in clinical practice. Methods: Literature was searched and perspectives from 10 healthcare professionals with experience in switching patients with T2D to OW semaglutide from another GLP‐1RA were collated. Results: Medical triggers for switching to another GLP‐1RA included HbA1c targets not being met, a desire for additional weight loss, poor adherence, patients moving to increased CV risk status and adverse effects with the current GLP‐1RA. Non‐medical triggers for switching included patient preference, cost, formulary changes and insurance mandates. Once the decision to switch is made, an individualised approach is recommended, based on considerations that include reimbursement requirements, treatment duration with (and dose of) previous GLP‐1RA, the patient's experience initiating the prior GLP‐1RA, any concomitant treatment and clinical characteristics. When switching, it is important to emphasise that treatment burden will not increase and that if gastrointestinal adverse effects occur, they are typically transient. Any transient gastrointestinal adverse effects that may occur (or recur) when switching to another GLP‐1RA can be reduced by slow up‐titration and advising patients to reduce food portion sizes and fat intake. Conclusion: Switching from one GLP‐1RA to another, such as OW semaglutide, can provide clinical benefits and may delay the need for treatment intensification. Abstract :